Spatial distribution pattern, bionomic, and demographic parameters of a new invasive species of armyworm Spodoptera frugiperda (Lepidoptera; Noctuidae) in maize of South Sumatra, Indonesia - Rudi Tomson Hutasoit; Septian Hary Kalqutny; I Nyoman Widiarta (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hutasoit RT, Kalqutny SH, Widiarta IN. 2020. Spatial distribution pattern, bionomic, and demographic parameters of a new invasive species of armyworm Spodoptera frugiperda (Lepidoptera; Noctuidae) in maize of South Sumatra, Indonesia. Biodiversitas 21: 3576-3582. The fall armyworm, Spodoptera frugiperda, has reportedly been found in Indonesia since 2019. The main hosts of this new invading insect are food crops and several other crops. This study aimed to examine the spatial distribution pattern, bionomic, and demographic parameters for developing a sampling plan and strategy to control the pest. The study was conducted by observing the total population of S. frugiperda on nine plots of maize plants weekly. The development of S. frugiperda from egg to adult was also observed in plastic containers (diameter of 4 cm x height of 8 cm) fed with maize in controlled room conditions (temperature = 29 ± 2.1°C, 74 ± 10.1% RH). Observations were made on several bionomic and demographic parameters. The results of the study showed that the S. frugiperda distributes in groups, and each group spreads with a low grouping rate. The life cycle of S. frugiperda occurs for an average of 25.11 days with a range of 24-26 days. The net reproduction rate (Ro) of S. frugiperda was 422.46 individuals/parent/generation. S. frugiperda‘s intrinsic rate of increase was 0.22 individuals/parent/day. The length of generation (T) and S. frugiperda doubling time (DT) were 26.59 and 3.04 days, respectively. This species has survived well on the maize in the new habitat, so it will threaten the food crops, especially the maize. A sampling plan can be developed based on spatial distribution parameters to monitor population density to implement a control threshold and control measures from the early stage of maize during adult pre-emergence.